The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0101-33002014000300008
|View full text |Cite
|
Sign up to set email alerts
|

Política municipal e acesso a serviços de saúde São Paulo 2001-2012, quando as periferias ganharam mais que o centro

Abstract: The study analyses the evolution of the supply and consumption of public healthcare services within the municipality of São Paulo between 2000 and 2012. In the period services offered grew and the disparity between the supply and consumption of public health services across the areas with the best and worst indices of income, education and health decreased. To explain these results we discuss the municipal policies adopted during the period and explore their relation with both electoral competition and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(12 reference statements)
0
3
0
2
Order By: Relevance
“…However, a study shows that, for a better adherence to prophylaxis, it does not suffice to provide medication to the users and schedule them to return 30 days later with no direct follow-up of the appropriate use of PEP. The importance of improving communication strategies and following these users through the duration of prophylaxis is emphasized (24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study shows that, for a better adherence to prophylaxis, it does not suffice to provide medication to the users and schedule them to return 30 days later with no direct follow-up of the appropriate use of PEP. The importance of improving communication strategies and following these users through the duration of prophylaxis is emphasized (24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2013 has shown that South and Southwest Brazil offered better conditions for access to health services to the populations (23) ; even so, these are exactly the areas whose municipalities have the highest rates of AIDS incidence, which highlights the need for considering expanding investment to enhance SUS and policies for fighting the epidemic. The state of São Paulo, a pioneer in establishing policies to fight STI, and especially HIV/ AIDS (24) , has been promoting the decentralization of actions to municipalities, which enables advances in SUS structure and is reflected in better access to health services (25) .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, by including more women, racial minorities, and poor people, the councils come much closer to reflecting Brazil's demographic profile than traditional representative institutions do (Coelho 2004;2007). Additionally, Coelho associates their existence to reductions in the inequality of service provision between rich and poor regions, as councils located in the periphery more intensively argued for devoting funds to the expansion of healthcare facilities, such as Health Units and hospitals (Coelho 2013;Coelho, Szabzon, and Dias 2014). However, she also finds that the health councils' existence is associated with a slight increase in inequality between poorer regions, which she ascribes to differences in the capacity to mobilize for funding (such as informal access to relevant governmental authorities).…”
Section: São Paulo's Participatory System In Healthcare Policymentioning
confidence: 99%
“…Tendo em vista a flagrante heterogeneidade das condições de vida e de atenção à saúde presentes nos diferentes recantos do território nacional, a necessidade de particularizar os achados dessa pesquisa se mostra de fundamental importância, sob pena de não se conseguir apreender essa diversidade de situações e, portanto, não se obter o conhecimento necessário para intervir adequadamente nos problemas e acompanhar o impacto das ações propostas. (COELHO;SZABZON;DIAS, 2014).…”
unclassified